Optimal congestion management in network routers subject to constraints, disturbances, and noise using the model predictive control approach - Nasiri, Bijan; Bayat, Farhad; Mohammadkhani, MohammadAli; Bartoszewicz, Andrzej (IET cyber-physical systems, 2024)
A predictive queue management method is proposed for constrained congestion control in internet routers in the face of communication delays. The proposed method uses the queue and router models, input traffic rate, and queue length to precisely characterise the entire process. The model that has been built is then used to construct an optimal constrained active queue management (CAQM) strategy using the model predictive control method. Important factors, such as link capacity, Transmission Control Protocol (TCP) sessions, round‐trip time, and a few others, have been selected and used to linearise the interconnection of TCP. Then, an efficient MPC‐based structure to manage the CAQM in the face of unknown disturbances is designed. Simulations are used to validate the proposed method's effectiveness and robustness.